2012
DOI: 10.2165/11631980-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity and Inter-Rater Reliability of an Instrument to Characterize Unintentional Medication Discrepancies

Abstract: The validity and reliability of the instrument developed to assess unintentional medication discrepancies at patient transition from the hospital to the community setting was found to be satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A systematic review from 2016 on the classification of discrepancies found that few studies used standardised taxonomies for classifying medication discrepancies, and most studies (60%) classified medication discrepancies empirically, based on the data collected 3 . We considered using one of the few standardised ways to categorise discrepancies 29,30 but found that our data were better described by using the categories found in a pilot study. We did, however, categorise the cause of the discrepancies into patient‐associated factors and system‐associated factors as is done in several other studies 5,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review from 2016 on the classification of discrepancies found that few studies used standardised taxonomies for classifying medication discrepancies, and most studies (60%) classified medication discrepancies empirically, based on the data collected 3 . We considered using one of the few standardised ways to categorise discrepancies 29,30 but found that our data were better described by using the categories found in a pilot study. We did, however, categorise the cause of the discrepancies into patient‐associated factors and system‐associated factors as is done in several other studies 5,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Claeys et al defined medication discrepancies as medication-related problems, while the MDT suggested that in the absence of a gold standard list, the term medication discrepancy may be more practical than the term medication error. While the items in Claeys tool may be assigned as unintentional medication discrepancies, the definition of medication discrepancy and the aim of the instrument were not clear [25]. This instrument was not used in any other studies in our review.…”
Section: Discussionmentioning
confidence: 99%
“…We identified three pre-defined/standardized taxonomies for classifying medication discrepancies resulting from medication reconciliation. They were the Medication Discrepancy Tool (MDT) (2004, USA) [23] , the APS-Doc classification (2012, Germany) [24], and a taxonomy for unintended medication discrepancy (2012, Belgium) [25]. The number of types of medication discrepancy in each tool was 19, 48, and 11 items, respectively.…”
Section: Classification Of Medication Discrepanciesmentioning
confidence: 99%
“…Medication discrepancies were categorized according to the Instrument to Characterize Unintentional Medical Discrepancy, 10 with the addition of errors in monitoring and omission that were not included in the instrument ( Table 2). Of the 106 total pharmacist recommendations, 1% showed incorrect route, 3% were missing length of treatment, 16% resulted from omission of a drug, and 6% were inappropriate additions of a drug, of which 17% resulted in an adverse drug event (ADE), defined as "an injury resulting from medical intervention related to a drug."…”
Section: Pharmacy Recommendationsmentioning
confidence: 99%